PELAKSANAAN PELAYANAN PUBLIK DI KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR TAHUN 2012 - Sriadi Purnama; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
One of the district that is in Rokan Hilir District Fort Babussalam formed on thebasis of Rokan Hilir District Number 27 Year 2011 About Fort Babussalam DistrictFormation.From the author of phenomena encountered in the field are the symptoms thatarise include: still less optimalnya public services provided by District officials to postpemekaran particular community management Identity Card (KTP), Family Card (KK),Erection of Building Permit (IMB) and Business Site Permit (SITU) are still long in thesolution. Still a lack of knowledge and skills possessed by the district head officeofficials to penyelenggarakan Fort Babussalam this rule in the case of lack of ability touse the apparatus in facilities and infrastructure such as typewriter and computer use.The purpose of this study was to find out how the implementation of the publicservice in the District of Fort expansion post Babussalam and to discover the obstaclesof public services in the District of Fort expansion post Babussalam. The authors usethe theory in this study that is using the theory of public service. The method used in thisstudy is qualitative, that scrutiny to explain data obtained from observations andexplain its purpose as well strengthen a theory, to obtain information about the currentsituation. Data collection techniques in this study is using interviews anddocumentation.Administrative Reform Minister's decision No. 63 of 2003 About GeneralGuidelines for Maintenance of Public Service Minister of Administrative Reform As tothe principles of public service includes several aspects namely simplicity, clarity,certainty time, accuracy, Peace, Responsibility, Equipment Facility and Infrastructure,facilities access, Kedisplinan, politeness and friendliness, and Leisure.Keywords: Implementation, Public Service and Fort Babussalam.